Adorno's positive dialectic - Sherratt, Yvonne, 1966- (Cambridge ; New York : Cambridge University Press, 2002)
This book offers a radically new interpretation of the work of Theodor Adorno. In contrast to the conventional view that Adorno's is in essence a critical philosophy, Yvonne Sherratt traces systematically a utopian thesis that pervades all the major aspects of Adorno's thought.
Cover; Half-title; Title; Copyright; Dedication; Contents; Preface; Abbreviations; General Introduction; Prelude to Adorno s Positive Dialectic; Prelude I Adorno s Intellectual Tradition: German Philosophy; Prelude II Adorno s Intellectual Tradition: Sigmund Freud; Adorno s Positive Dialectic; PART I NEGATIVE THESIS; PART II POSITIVE THESIS; Bibliography; Index.
Includes bibliographical references (pages 240-248) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Adorno, Theodor W., -- 1903-1969.; Adorno, Theodor W., -- 1903-1969; PHILOSOPHY -- History & Surveys -- Modern